Modelagem do canal de descargas atmosféricas utilizando a teoria de linhas de transmissão - Thiago Candido Moratti Cardoso (2014)
In this work an investigation is presented on the representation of the lightning return-stroke channel using transmission line theory, with focus on models that treat the return-stroke current as the result of the discharge to ground of an initially charged line. Models available in the literature that use this representation were presented, implemented and analyzed. The consistency of the evaluated models was tested by checking the assumptions made by the authors in their original works. Additional studies were made to identify the main potentialities and limitations of this type of representation for the lightning channel. To overcome some of the limitations identified in the investigated models, a return-stroke model based on transmission line theory was formulated. This model used the Charge Simulation Method for calculating the per-unit-length capacitance of the line, with the inductance being calculated from the assumed propagation speed and the previously calculated capacitance values. The per-unit-length resistance of the line was assumed to be nonlinear and time variant. For such, an equation based on the radial expansion of spark channels was used. Corona was taken into account by means of a simplified approach based on a coaxial geometry, assuming that the accumulation of charges in the vicinity of the lightning channel can be represented as an increase in the line capacitance. The proposed model was shown to be able to reproduce with reasonable accuracy currents and electromagnetic fields associated with subsequent strokes of lightning.